Effects of atmospheric pollutants on human health and deterioration of medieval historical architecture (North Africa, Tunisia) (2021)
Air pollution is a factor of concern on a global scale, accelerating the deterioration of historic medieval architecture and having harmful effects on human health. The general objective of this study is to understand the risks of atmospheric contamination that contribute to the degradation of the medieval historical heritage of (1) Bab El Bhar, (2) the Tunis Train Station and (3) the Bardo National Museum, in the City of Tunis, capital of Tunisia, located in North Africa. Sequentially, 64 samples were collected in SMPSs and 64 of dust particles in sites 1, 2 and 3, from 2015 to 2019. Field Emission Scanning Electron Microscopy (FE-SEM) was utilized together with High Resolution Transmission Electron Microscopy (HR-TEM) and the coupled with an Energy Dispersive X-ray (EDS), which allowed a better characterization and identification of NPs in images, using Energy Dispersive X-ray (EDS). The Bab El Bhar SMPS samples yielded a higher proportion of ultrafine and organic particles. Sedimented dusts showed high proportions of organometallic particles (Al, As, Ba, Ca, Cd, Co, Cr, Fe, K, Mg, Mn, Mo, Na, Ni, Pb, S, Sb, Se, Si, Sn, Ti, V and Zn). The need to create public policies to protect both human health and physical historic infrastructure is noted, as this study identified dangerous elements harmful to human health in ultrafine particles, easily suspended by the wind and highly corrosive to historical buildings from the medieval period in the air of a busy metropolitan tourist site.